A Transcriptome Sequencing Study on Genome-Wide Gene Expression Differences of Lung Cancer Cells Modulated by Fucoidan - Zhao, Yanjie; Li, Xinmei; Zhang, Heng; Yan, Mingzhe; Jia, Mengmeng; Zhou, Qihui (Frontiers in Bioengineering and Biotechnology, 2022)
Fucoidan has received increasing attention in anti-(lung) tumors. However, the effect of fucoidan on the gene changes of lung cancer cells (LCCs) has not been examined systematically. Herein, we investigate the effect of fucoidan on the phenotypes of LCCs and their gene expression by transcriptome sequencing analysis. The phenotypes of LCCs are significantly inhibited by fucoidan. Importantly, compared to LCCs, 1 mg/mL fucoidan has no effect on the phenotypes of normal cells. Further, 6,930 differentially expressed genes (DEGs) in the transcriptome of LCCs (3,501 up-regulated and 3,429 down-regulated genes) are detected via RNA-sequencing between the fucoidan and control groups. Gene Ontology analysis confirms that DEGs are reflected in DNA replication, cell-substrate junction, regulation of cell cycle phase transition, apoptosis, focal adhesion, cadherin binding, and cell adhesion molecule binding. Thus, our findings on the transcriptomic level highlight the therapeutic potential of fucoidan for lung cancer treatment.